Prevalence and severity of gingivitis in school students aged 6–11 years in Tafelah Governorate, South Jordan: results of the survey executed by National Woman's Health Care Center. (December 2015) - Rodan, Rania; Khlaifat, Feryal; Smadi, Leena; Azab, Reem; Abdalmohdi, Asma
Abstract Background A cross-sectional census was conducted on 994 public school students aged 6-11 years living in 3 different parts of Tafeleh Governorate—South of Jordan, to determine the prevalence, and severity of gingivitis and to evaluate the oral hygiene habits among them as a part a survey executed by National Woman's Health Care Center. All students were examined for gingival index (GI) and plaque index (PI), information about oral hygiene habits was recorded. Results Only 29.8 % had healthy gingiva, 38.5 % had mild gingivitis, 31.4 % had moderate gingivitis, and 0.3 % had severe gingivitis. The difference between both genders was not statistically significant P > 0.05. 36.8 % of the examined students never brushed their teeth. Average gingival index (GI) and average plaque index (PI) were 0.77 and 0.61 respectively. Conclusions Fair oral hygiene with mild to moderate gingivitis is highly prevalent among Tafelah school children. This study indicated that oral health status among schoolchildren in Tafelah is poor and needs to be improved. Long-term school based oral health education programme is highly recommended.